Cartilage intermediate layer protein affects the progression of intervertebral disc degeneration by regulating the extracellular microenvironment (Review) - Liu, Libangxi (Int J Mol Med, 2021)
Intervertebral disc degeneration (IDD), which is caused by multiple factors, affects the health of individuals and contributes to low back pain. The pathology of IDD is complicated, and changes in the extracellular microenvironment play an important role in promoting the process of degeneration. Cartilage intermediate layer protein (CILP) is a matrix protein that resides in the middle of human articular cartilage and is involved in numerous diseases that affect cartilage. However, there is no detailed review of the relationship between CILP and degenerative disc disease. Growing evidence has revealed the presence of CILP in the extracellular microenvironment of intervertebral discs (IVDs) and has suggested that there is a gradual increase in CILP in degenerative discs. Specifically, CILP plays an important role in regulating the metabolism of the extracellular matrix (ECM), an important component of the extracellular microenvironment. CILP can combine with transforming growth factor-β or insulin-like growth factor-1 to regulate the ECM synthesis of IVDs and influence the balance of ECM metabolism, which leads to changes in the extracellular microenvironment to promote the process of IDD. It may be possible to show the correlation of CILP with IDD and to target CILP to interfere with IDD. For this purpose, in the present study, the current knowledge on CILP was summarized and a detailed description of CILP in discs was provided.